Lignin from hydrolyzed wood by-product as an eco-friendly emulsion stabilizer - Livcha, Sandra; Shulga, Galia; Zhilinska, Elina; Neiberte, Brigita; Verovkins, Anrijs; Vitolina, Sanita; Viksna, Arturs (International Conference “Environmental Engineering”, 2017)
Aspen sulfur free soda lignin was obtained as a result of alkaline delignification of hydrolyzed sawdust, a by-product of wood mechanical processing. The pre-hydrolysis of aspen sawdust was performed for enhancing the yield of lignin from the wood residue as well as to decrease the energy consumption of its milling for obtaining a filler for composites. The obtained lignin was characterized by a chemical composition, particle sizes and zeta potential values as well as by the surface-active properties at the air-water and oil- water interfaces. The surface tension of the lignin solutions at the air-water interface decreases with dropping рН values and increasing lignin concentration due to hydrophobization of the lignin macromolecules, which is strengthened in the presence of a low molecular salt. The study of the obtained lignin as an emulsion stabilizer has shown that the O/W emulsion stabilized with alkaline lignin solutions with a concentration less than 0.1% demonstrates the highest stability with the formed smallest emulsion particles, having the highest negative charge, but the stabilization proceeds via the electrostatic mechanism. With decreasing pH values and increasing lignin concentration in the emulsion, the stabilization mechanism is more complicated with a growing role of steric factors.
Keywords: aspen soda lignin; O/W emulsion stabilization; surface-active properties